The concessionary fares as a marketing tool of Malayan railway (Keretapi Tanah Melayu) / Rosmairi Ghazali - Ghazali, Rosmairi (1989)
Malayan Railway is a sole rail carrier in Malaysia, During the early years of rail transport launched, there is no competent competitor to rail transport. This is because other carrier such as road and air still under developed. Therefore, it gave advantages to rail transport. , However, road transportation, which have become increasingly popular, become a serious competitor to the railway as an alternative transport agency for the carriage of freights and passengers. This competition . arose because the configuration of the country dictated almost parallel development of road and railway systems, particularly in the western half of the peninsula. In order to maintain and make rail transport attractive to public, MR introduced several types of concession fares to achieve a set of objectives. It covers passenger and freight. As a government agency, this is parallel to government policy which is more on public obligations rather than profit making organization. In order to acknowledge public regarding the services offered, MR had designed several types of promotional campaign such as pamphlets, signboards and advertisement through electronic media. Therefore, the research is to extract the effectiveness of the marketing tools and is the concession fares are fully utilized by the eligible passengers.